Promising Treatment Options for Axial Spondyloarthritis: An Overview of Experimental Pharmacological Agents - Tahir H; Byravan S; Fardanesh A; Moorthy A (Dove Medical Press, 2021)
Hasan Tahir,1,2 Swetha Byravan,3 Armin Fardanesh,4 Arumugam Moorthy3,5 1Department of Rheumatology, Royal Free London NHS Foundation Trust, London, UK; 2Division of Medicine, University College London, London, UK; 3Department of Rheumatology, University Hospitals of Leicester NHS Trust, Leicester, UK; 4Department of General Medicine, Royal Free London NHS Foundation Trust, London, UK; 5College of Life Sciences, University of Leicester, Leicester, UKCorrespondence: Hasan TahirDepartment of Rheumatology, Royal Free London NHS Foundation Trust, London, UK, Division of Medicine, University College London, London, UKEmail hasan.tahir@nhs.netAbstract: Axial spondyloarthritis (axSpA) is a chronic inflammatory condition that predominantly affects the axial skeleton. All patients receive conservative management measures which include physiotherapy, patient education and use of nonsteroidal anti-inflammatory drugs (NSAIDs). Those with significant active disease will require escalation of their treatment with the use of biologics. Currently, there are five approved TNF inhibitors and two approved IL-17 inhibitors for use in axSpA. However, despite this up to 40% of patients do not respond or are intolerant to current available treatment. This leaves a significant number of patients with uncontrolled disease and unmet need for additional therapies. Though many drug classes have been trialed for axSpA they show poor efficacy; however, over the last few years there are three which demonstrate much greater promise as novel therapies for axSpA, these include dual neutralization of IL-17A and IL-17F, Janus kinase (JAK) inhibitors, and granulocyte-macrophage colony-stimulating factor (GM-CSF) inhibitors. This article reviews the evidence for these novel emerging therapeutic options for axSpA.Keywords: Axial spondyloarthritis, novel therapies, JAK inhibitors, IL-17 inhibitors, GM-CSF inhibitors